Tax Planning: Analysis Of Its Effect On Income Smoothing In Consumer Cyclicals Companies 2017-2022 Period - Khairunnisa’, Qatrin Anggun; Aisyaturrahmi (International Economic Conference of Business and Accounting, 2024)
One of the factors that influence companies to carry out income smoothing measures is tax planning. The purpose of this study is to determine the effect of tax planning on income smoothing both before and during the Covid-19 pandemic. The data used in this research is secondary data. The population in this study are Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. The data is taken from the company’s annual report. The sample in this study was 138 consisting of 23 companies for the 2017-2022 period after being selected using the stratified sampling method. This study uses logistic regression analysis techniques to prove the hypothesis assisted by SPSS 23 software. The results show that tax planning has an effect on income smoothing both before and during the Covid-19 pandemic. This research is expected to contribute to companies in predicting opportunities for income smoothing practices in financial statements, to help investors to be more careful in choosing companies, and to serve as a reference for future research using populations and other variables